A Model For The Fuzzy Front End Of New Product Development Process - Abd Rahman, Md Nizam (2016)
In general, New Product Development (NPD) methodology can be broken down into five phases, Strategic Planning. Idea Generation, Pretechnical Evaluation, Technical Development, and Commercialization. The first three steps are known as the front end and the last two are known as the back-end of the NPD methodology. The scope of this research work is limited to the first two steps of the NPD methodology, which are strategic planning and idea generation. The objectives of this research work are I) to piece together the various steps required in executing strategic planning process to ensure its effectiveness and 2) to define guidelines in selecting idea generation techniques that are suitable for a given set of conditions. Through analyzing case studies on thirty cornpapies that have been proven successful in NPD programs, the main factors that have significant impact on the success of NPD strategic planning process are verified and guidelines for selecting suitable idea generation techniques for a given set of conditions are developed.